Good practices in cultural heritage management and the use of subsurface knowledge in urban areas. (2017) - de Beer, Johannes; Boogaard, Floris
Abstract: City growth threatens sustainable development of cities. Over the past decades increased urbanization has created more pressure - not only on the suburban outskirts - but also in the inner core of the cities, putting important environmental issues such as water management and cultural heritage under stress. Cultural heritage, either standing monuments or archaeological remains, is internationally recognized as an important legacy of our history. The European Convention on the Protection of the Archaeological Heritage incorporates concepts and ideas that have become accepted practice in Europe. Conservation and enhancement of archaeological heritage is one of the goals of urban planning policies. One of the key objectives of the European policy is to protect, preferably in-situ, archaeological remains buried in the soil or seabed and to incorporate archaeological heritage into spatial planning policies. Conflicts with prior uses and unappreciated impacts on other subsurface resources, amongst them archaeological heritage, make use of underground space in cities suboptimal. In terms of ecosystem services, the subsurface environment acts either as a carrier of archaeological heritage in situ (stewardship) or supports above-ground cultural heritage. Often, it's not enough to protect the heritage site or monument itself: new developments outside a specific protected area can lead to changes in groundwater level, and cause serious damage to heritage buildings and archaeological deposits. This paper presents good practices in cultural heritage management and the use of subsurface knowledge in urban areas.